The phenomenon of anticipation in fencing. An applicability approach - Borysiuk, Zbigniew; Konieczny, Mariusz; Błaszczyszyn, Monika; Błach, Wiesław; Obmiński, Zbigniew (Frontiers in Sports and Active Living, 2024)
The aim of the study was to determine the structure of muscular activity and ground reaction forces during the preparatory period and the execution of a fencing lunge at the opponent's torso. The analysis focused on the correlations between three phases of a fencing technical action in the context of factors of temporal anticipation. Six female épée fencers from the Polish National Fencing Team participated in the study. The research tools included electromyography (EMG), ground reaction force (GRF) platforms, and the OptiTrack motion capture system. The fencers performed the lunge three times in response to visual cues from the coach. By integrating the testing system, the EMG signal indices of the fencers' upper and lower limbs and the vertical force values of the fencers' front and rear leg muscles were obtained simultaneously. The results of the study demonstrated the key role of five muscles: BICEPS BRACHII, LAT TRICEPS, EXTCARP RAD, BICEPS FEMORIS and MED GAS in influencing the speed of lunge execution. In addition, a significant correlation was found between the EMG signal of the gastrocnemius muscle of the rear leg and the movement time (MT) phase of the lunge execution. The anticipatory activation of the EMG signal in relation to the vertical force waveforms generated by the ground forces response platform in the 15-30 ms interval was demonstrated. Finally, the importance of the preparatory period for the effectiveness of the fencing lunge was highlighted based on the phenomenon of anticipation.